The poetics of space in an opera for children, in digital pills - Karen Acioly; Cristina Rego Monteiro da Luz (Kalagatos, 2024)
This article focuses on opera for children, taking a broad overview across time and space. The aim of the research is to identify what constitutes opera for children by embracing its dramaturgical, poetic, imagistic, and symbolic aspects. The chosen approach was sensitive listening to children, and alongside this, exploring important aspects of theory and practice. A case study was used as a framework for analysis — the creative process of the children's opera Bem no Meio, which served as the basis for the production of mini-documentaries in digital snippets. These mini-docs provide pedagogical support for raising awareness and educating students, parents, teachers, and new audiences. They were intended to generate a visual literature of opera for children, a genre that is still little disseminated and studied in Brazil. The research incorporated concepts from the phenomenology of the imagination, particularly those of Gaston Bachelard (2008).